2011
DOI: 10.1186/1472-698x-11-14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge levels amongst village AIDS committees after undergoing HIV educational sessions: results from a pilot study in rural Tanzania

Abstract: BackgroundVillage AIDS committees (VAC) were formed by the Tanzanian government in 2003 to provide HIV education to their communities. However, their potential has not been realised due to their limited knowledge and misconceptions surrounding HIV, which could be addressed through training of VAC members. In an attempt to increase HIV knowledge levels and address common misconceptions amongst the VACs, an HIV curriculum was delivered to members in rural north western Tanzania.MethodsAn evaluation of HIV knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This result is in consonance with other studies elsewhere. [8][9][10][11][12][13] In Raigad district of India, respondents below 20 years of age were also less likely to have comprehensive knowledge of HIV compared to those with older ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in consonance with other studies elsewhere. [8][9][10][11][12][13] In Raigad district of India, respondents below 20 years of age were also less likely to have comprehensive knowledge of HIV compared to those with older ages.…”
Section: Discussionmentioning
confidence: 99%
“…This result correlates with several findings. [8][9][10][11][12][13] A study conducted in Kenya, Swaziland, Zimbabwe, Tanzania, Lesotho, Malawi and Uganda also reported that urban women had greater knowledge of HIV prevention compared to rural women. 12 Respondents with primary and secondary+ (OR=1.63) 95% CI=1.34-1.99) (OR=3.6) 95% 2.86-4.58) respectively had significant (p=0.000) higher odds of having comprehensive knowledge compared to those with no education.…”
Section: Discussionmentioning
confidence: 99%
“…However, once established, these groups need ongoing and substantial support, including regular training, if they are to become a more widely recognised source of accurate information for the local community, particularly since previous research has shown that committee members themselves often hold inaccurate HIV and ART-related beliefs that can be disseminated through the community [10,18]. …”
Section: Discussionmentioning
confidence: 99%
“…The large number of FGDs utilised in this study and the stratification of communities to include rural, urban and high-risk increases the representativeness of our findings, and makes this one of the largest studies of its kind. 23 24 However, although large, representative and inclusive, this study is not without limitations.…”
Section: Discussionmentioning
confidence: 93%
“…These misconceptions date back to the very early days of the HIV epidemic and it is disappointing that they persist despite the substantial and varied community information campaigns that have been implemented over the past two decades. 23 25 …”
Section: Discussionmentioning
confidence: 99%